Application of transfer matrix and transfer function analysis to grating-type dielectric laser accelerators: Ponderomotive focusing of electrons - Andrzej Szczepkowicz (Physical Review Accelerators and Beams, 2017)
The question of suitability of transfer matrix description of electrons traversing grating-type dielectric laser acceleration (DLA) structures is addressed. It is shown that although matrix considerations lead to interesting insights, the basic transfer properties of DLA cells cannot be described by a matrix. A more general notion of a transfer function is shown to be a simple and useful tool for formulating problems of particle dynamics in DLA. As an example, a focusing structure is proposed which works simultaneously for all electron phases.